Delamanid suppresses CXCL10 expression via regulation of JAK/STAT1 signaling and correlates with reduced inflammation in tuberculosis patients - Qiao, Min; Li, Shanshan; Yuan, Jinfeng; Ren, Weicong; Shang, Yuanyuan; Wang, Wei; Liu, Rongmei; Zhang, Fuzhen; Li, Qing; Wu, Xiao; Lu, Jie; Gao, Mengqiu; et al. (Frontiers in Immunology, 2022)
Background: Apart from bactericidal effects, anti-tuberculosis drugs can interfere with the host’s immune system. In this study, we analyzed the role of delamanid (DLM), an inhibitor of mycolic acid synthesis of mycobacterial cell wall, on human macrophages. Methods: Based on a cohort of multidrug-resistant tuberculosis (MDR-TB) patients treated with DLM, the levels of C-reaction protein (CRP) and cytokines in the plasma were monitored using immunoturbidimetric assay and flow cytometry, respectively. We investigated the role of DLM on CXCL10 expression in U937 cell model using the following methods: cell viability assay, reverse transcription-quantitative polymerase chain reaction, enzyme linked immunosorbent assay, immunoblot, and transwell co-culture assay. Results: A total of 23 MDR-TB patients were included, comprising of 13 patients treated with optimized background therapeutic regimen (OBR) plus DLM regimen (OBR+DLM) and 10 patients treated with OBR plus placebo. DLM administration was associated with a significant reduce in circulating CRP level. Correspondingly, after treatment, the level of CXCL10 in patients treated with OBR+DLM was significantly lower than that with control. Using cell model, DLM dramatically suppressed CXCL10 expression, which majorly depended on inhibiting the JAK/STAT pathway, and impaired the migration of PBMCs. Conclusion: Our data firstly demonstrate that DLM suppresses CXCL10 expression via regulation of JAK2/STAT1 signaling and correlates with reduced inflammation in MDR-TB patients. DLM could be used as a potential drug for immunotherapy of patients with overactive immune response due to CXCL10.